The Impact of Advertising Appeal and Celebrity Endorse on Attitude Advertising with Purchase Intention as Mediation Variable on Lifebuoy Hand Washing Soap Advertisement on Television - Novia Elvi Zikri; Vidyarini Dwita (Marketing Management Studies, 2021)
Today’s very high level of competition and increasing knowledge and public awareness of health make hand washing soap producers compete in promoting their product through advertisements on television, as well as made by the manufacturer of hand soap brand Lifebuoy, an interisting advertisement is advertising that has appeal, the ability to attract market attention (audiance) target. The messages to be conveyed can be presented in a stylishdifferent delivery, in addition to having an advertising appeal, it is also necessary using a model or celebrity to get people to remember the product in the ad. A calebrity is a person who has high popularity and has a strong influence, the popularity possesed by the endorser becoms a strong influence in attracting attitudes people towards advertising, a good attitude will foster a consumer’s purchase intention. This study aims to see how the attractiveness, celebrity endorsement of attitude advertising and purchase intention on Lifebuoy hand soap on TV to household actors in the city of Padang by distributing 200 questionnaires, and using the Partial Least Square (PLS) test, whare the findings in this study is (1). The attractiveness of advertising has a positive and significant influence on purchase intention, (2). The attractiveness of advertising has non-positive and significant effect on attitude advertising, (3). Celebrity endorse has a positive and significant influence on purchase intention, (4). Celebrity endorse has a negative effect and significant to attitude advertising, (5). Attitude advertising has a significant influence positive and significant to purchase intention. From this research attitude as a variable mediation does not have a moderating rele non mediation.